Quality evaluation of citrus varieties based on phytochemical profiles and nutritional properties - Guo, Huan; Zheng, Yin-Jian; Wu, Ding-Tao; Du, Xu; Gao, Hong; Ayyash, Mutamed; Zeng, De-Guang; Li, Hua-Bin; Liu, Hong-Yan; Gan, Ren-You (Frontiers in Nutrition, 2023)
Introduction China is one of the major producers and exporters of various kinds of citrus fruits. As one of China’s major citrus planting bases, Sichuan has a citrus planting area that exceeds 400,000 hectares. Meanwhile, citrus cultivation has become one of the important agricultural pillar industries in the region. Citrus fruits are reported to show various health-promoting effects, especially antioxidant activity. However, reports on the functional, nutritional and qualitative characteristics of different citrus varieties in Sichuan are still scarce. Methods The quality attributes (color parameters, shape, and size), juice properties (titratable acids and total soluble sugar), mineral elements, and health-promoting nutritional and functional components (protein, carbohydrates, fat, dietary fiber, ascorbic acid, phenolic acids, and flavonoids), as well as antioxidant properties of 10 typical citrus varieties cultivated in Sichuan, were systematically investigated and analyzed. Results and Discussion Significant differences among different citrus varieties were found. In particular, the total soluble sugar content of Mingrijian was higher than that of other citrus, suggesting its potential for fresh consumption and food processing. Moreover, a total of five flavonoids and nine phenolic acids were identified and quantified. Yuanhong, with higher contents of ascorbic acid and phenolic acids, was considered to be a valuable variety with excellent antioxidant capacity and can be used for value-added processing in the food industry. Principal component analysis and hierarchical cluster heatmap analysis suggested that there were significant differences among the 10 citrus varieties. Correlation analysis confirmed the significant contribution of ascorbic acid and phenolic acids to antioxidant capacity in citrus. The results can provide some references for the cultivation and selection of nutritious citrus fruits.